2013
DOI: 10.1016/j.jmb.2013.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Highly Active Folding Enzyme by Combining a Parvulin-Type Prolyl Isomerase from SurA with an Unrelated Chaperone Domain

Abstract: Parvulins are small prolyl isomerases and serve as catalytic domains of folding enzymes. SurA (survival protein A) from the periplasm of Escherichia coli consists of an inactive (Par1) and an active (Par2) parvulin domain as well as a chaperone domain. In the absence of the chaperone domain, the folding activity of Par2 is virtually abolished. We created a chimeric protein by inserting the chaperone domain of SlyD, an unrelated folding enzyme from the FKBP family, into a loop of the isolated Par2 domain of Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…PPIase domain P1 is packed against the core structure of the N- and C-terminal domains and does not show significant activity, while the more active P2 domain extends away from the core structure [77,80,81] . The PPIase activity of P2 has been shown to be increased in the presence of the adjacent chaperone domain, presumably as this domain facilitates substrate binding close to the active site of P2 [82] . Deletion of both PPIase domains, however, did not cause a significant loss of SurA function in vivo and the isolated PPIase domains failed to complement activity in surA deletion mutants [81] .…”
Section: Omp Biogenesis In Vivomentioning
confidence: 99%
“…PPIase domain P1 is packed against the core structure of the N- and C-terminal domains and does not show significant activity, while the more active P2 domain extends away from the core structure [77,80,81] . The PPIase activity of P2 has been shown to be increased in the presence of the adjacent chaperone domain, presumably as this domain facilitates substrate binding close to the active site of P2 [82] . Deletion of both PPIase domains, however, did not cause a significant loss of SurA function in vivo and the isolated PPIase domains failed to complement activity in surA deletion mutants [81] .…”
Section: Omp Biogenesis In Vivomentioning
confidence: 99%
“…Chaperone activity has been reported only for two other microbial single-domain PPIases, cyclophilin LdCyP from Leishmania donovani and FKBP AvfkbX from Azotobacter vinelandii (56,57). Different chimeric PPIases with additional chaperone domains have been shown to be very efficient and fast in protein refolding, which may be interesting for various applications (61,62 We also found that FkpA positively influences the activity of CS in vitro, in particular at lower temperatures (Fig. 5).…”
Section: Discussionmentioning
confidence: 59%
“…This is in good agreement with a proposal of (Budiman et al, 2009), in which the non-PPIase domain is important to facilitate an efficient binding to a protein substrate and therefore maximize the ability of PPIase to catalysis the cis-trans isomerization. To note, some reports also highlighted the ability of parvulin in accelerating the refolding rate of RNase T1 (Kale et al, 2011;Scholz et al, 1997;Uchida et al, 1999;Geitner et al, 2013;Behrens et al, 2001;Vitikainen et al, 2004). Nevertheless, (Scholz et al, 1997) highlighted that the affinity of parvulin towards RNase T1 is generally weak and therefore, the catalytic efficiency towards this substrate is 100-fold lower, or more, than that of against a peptide substrate.…”
Section: Discussionmentioning
confidence: 99%